Isolasi dan Identifikasi Bakteri Pelarut Fosfat pada Tanah Ultisol di Kecamatan Rumbai, Pekanbaru - Oksana Oksana; Mokhamad Irfan; Annisa Ramadhani Fianiray; Syukria Ikhsan Zam (Perkumpulan Agroteknologi/Agroekoteknologi Indonesia, 2020)
Phosphate-solubilizing bacterial can fulfill the low available of soluble P on Ultisol. This research aimed to study on the quantity of the population bacteria and identify phosphate-solubilizing bacteria on Ultisol from Rumbai District, Pekanbaru. The research method used was descriptive method. Soil sample was collected from teak plantations of PT. Air Jernih, Sub district of Rumbai Pesisir, Pekanbaru and identification of phosphate-solubilizing bacteria was conducted in Laboratory of Pathology, Entomology and Microbiology, Faculty of Agriculture and Animal Husbandry, Universitas Sultan Syarif Kasim State Islamic, Riau from May-September 2017. The observed parameters were bacterial cell numbers, phosphate solubilization index, microscopic and biochemical characteristics. Four isolates were obtained with cell numbers ranging from 4.2 x 105 – 7.1 x 105 CFU/g of soil. All isolates showed the ability to dissolve phosphate with phosphate solubilization index ranging from 1.16 – 1.57. The four isolates were identified as Klebsiella (IBJ1 and IBJ2), and Acinetobacter (IBJ3 and IBJ4).